2004
DOI: 10.1021/jp0465276
|View full text |Cite
|
Sign up to set email alerts
|

Core-Level Shift of Si Nanocrystals Embedded in a SiO2 Matrix

Abstract: It is expected from existing theories that the core level of Si nanocrystals (nc-Si) embedded in a SiO2 matrix should shift toward a higher binding energy as compared to that of bulk crystalline Si due to quantum size effect. Indeed, it is observed in X-ray photoemission experiments that the Si 2p core level shifts to a higher apparent binding energy by 1−2 eV for all five oxidation states of Si n + (n = 0, 1, 2, 3, and 4) in the material system of SiO2 containing nc-Si. However, it is found that the core-lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 25 publications
1
44
2
Order By: Relevance
“…The reduction in intensity of the Si 0 peak may be attributed to oxidation due to residual oxygen in the nitrogen atmosphere. 8 Comparison of the as-grown sample with the sample annealed at 1100°C for 30 min showed that annealing shifted the Si 2p 0 peak position to a lower binding energy at 0.2 eV ͑Ϯ0.1͒. This decrease in binding energy between the as-grown sample and the heat-treated sample with a silicon fraction of 70% is also observed in samples with 50 and 60% silicon.…”
Section: B Chemical States Present In the Samplesmentioning
confidence: 81%
See 2 more Smart Citations
“…The reduction in intensity of the Si 0 peak may be attributed to oxidation due to residual oxygen in the nitrogen atmosphere. 8 Comparison of the as-grown sample with the sample annealed at 1100°C for 30 min showed that annealing shifted the Si 2p 0 peak position to a lower binding energy at 0.2 eV ͑Ϯ0.1͒. This decrease in binding energy between the as-grown sample and the heat-treated sample with a silicon fraction of 70% is also observed in samples with 50 and 60% silicon.…”
Section: B Chemical States Present In the Samplesmentioning
confidence: 81%
“…6,7 The main expectations include longer retention, lower gate voltage, and lower power consumption. 8 In addition, the discontinuity between the nanocrystals can prevent lateral charge loss and can also result in short writing times at lower voltages, as well as improved reliability. 9,10 Both injection and retention of electrons in these devices are very sensitive to the size, distribution, interfaces, and electronic structure of the nanocrystals.…”
Section: A Si Nanoparticles In Siomentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in contrast to the assumption in our calculation, the Si 2p core levels may shift somewhat with changing thickness, relative to the vacuum level. 26 Strain can also shift and split levels. 27 There is evidence that the Si template layer contains a small amount of innate strain, perhaps as much as 0.3%, 28 because of the Si/oxide interface.…”
Section: Resultsmentioning
confidence: 99%
“…This decrease suggests that Si-nc shell is mainly formed from suboxides and all the detectable SiO 2 bonds are replaced to form the shell of Si nanocrystals and Al 2 O 3 matrix [47]. In a similar study, Liu et al Chen et al measured a decrease of 0.6 eV in the binding energy of the core electrons of nanocrystalline Si with respect to crystalline Si , which is in the opposite direction than expected from the quantum confinement effect [57]. They used the C 1s signal exists due to the carbon contamination on the surface of the films as reference.…”
Section: X-ray Photoelectron Spectroscopymentioning
confidence: 91%